2001
DOI: 10.1111/j.1348-0421.2001.tb02634.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Antibiotics in Injured Coliforms Isolated from Drinking Water

Abstract: Abstract:We studied the antibiotic sensitivity of injured coliforms isolated from drinking water of La Plata, Argentina. The antibiotic sensitivity test by the agar diffusion method were proved in: Klebsiella oxytoca (14 strains), Enterobacter aerogenes (4 strains) and Enterobacter cloacae genomic group 3 (14 strains). We found that while these impaired total coliforms were sensitive to piperacillin-tazobactam (TAZ), netilmicin (NTL), ofloxacin (OFLX), and norfloxacin (NFLX) (100%), they had resistant to amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Even when only one ampicillin-resistant Escherichia coli strain was isolated from drinking water in our work, other authors from Germany (Schwartz et al, 2003) and from Argentina (Córdoba et al, 2001) have found many strains resistant to several antibiotics in the same kind of samples.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Even when only one ampicillin-resistant Escherichia coli strain was isolated from drinking water in our work, other authors from Germany (Schwartz et al, 2003) and from Argentina (Córdoba et al, 2001) have found many strains resistant to several antibiotics in the same kind of samples.…”
Section: Discussioncontrasting
confidence: 55%
“…The presence of several antibiotic compounds in both sewage treatment plants effluents and surface waters result most likely from applications in human medicine than from veterinary uses (Hirsch et al, 1999). Added to this fact, bacteria with acquired resistance have been also found in surface water, ground water, and drinking water in different countries (McKeon et al, 1995;Schwartz et al, 2003;Córdoba et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regrowth of these species can decrease water quality and generate public health problems Có rdoba et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacteria may be more resistant than indicator bacteria to chlorine and may even overgrow indicator bacteria, creating a veiled threat [8] . Moreover, a previous study revealed that injured bacteria can also harbor antimicrobial resistance [9] .…”
Section: Introductionmentioning
confidence: 99%